"Punk anarchy in the land of the sun": The punk movement in Paraíba of the redemocratization (1988-1998) (TEL Tempo, Espaço e Linguagem, 2023)
This research deals with punk rock and its existence in Paraíba at the time of Brazilian re-democratization, between 1988 and 1998, leading to the historiographical debate of the underground movement in Paraíba. Punk rock is a popular movement that spread in England as a reaction to the exhaustion of social movements and youth to neoliberal policies. Young people with no future perspective wielded their guitars, played the few chords they knew, and started punk rock. This article works with the concepts of Historical Materialism, Globalization, Urbanization, and, methodologically, Oral History. The bands with which we work are groups chosen under the criterion of being important bands for the history of the Paraíba underground.